From sea to the shore: Texts, traditions and the maritime practices in the western Indian Ocean, 1600–1800 AD. (3rd July 2021) - Chowdhary, Mir Kamruzzaman
ABSTRACT: When it comes to the maritime history of the Indian Ocean Region (IOR), there are few available textual resources and written pieces of evidence which can help undertake a cogent reconstruction. This article attempts to retrieve some of those maritime practices that prevailed among the mariners and sailors on the basis of a few available written documents, such as travellers' accounts, Mughal court chronicles, European factory records and other written documents. Such historical reconstruction is important since, in the past few decades, the Indian Ocean has become significant object of study in its own right. The article seeks to recover "forgotten" oceanic histories of law or practices in the western IOR, and examine how these got institutionalised as admiralty law in India. More precisely, it focuses on the process of the transformation of maritime law from tradition to admiralty law in some detail.